The influence of methoxy side groups and halogen nature on the mesomorphic and optical properties of symmetrical azomethines. Issue 5 (9th April 2017) - Perju, Elena; Cozan, Vasile; Timpu, Daniel; Bruma, Maria
ABSTRACT: The preparation, characterisation, thermotropic and optical properties of low-molecular azomethines with or without methoxy side group are described in this paper. The azomethine compounds were synthesised by condensation reaction of o -dianisidine/benzidine with para -halogen substituted benzaldehyde. Their properties were analysed by differential scanning calorimetry, thermogravimetry analysis, polarised optical microscopy, X-ray diffraction and optical spectroscopy. The azomethines present liquid crystalline behaviour with large mesophase range and high thermal stability. The compounds without lateral methoxy groups showed smectic A phase, while those with methoxy groups exhibited only nematic phase. The effect of methoxy group and different terminal substituents on the mesomorphic behaviour, molecular and optical properties was estimated in terms of parameters such as molecular polarisability, dipole moment, interdigitation parameter and axial ratio. GRAPHICAL ABSTRACT: